Analysis of Heavy Metal Cadmium (Cd) Content in Snakehead Fish (Channa striata) from Lake Rawa Taliwang - Alya Septiana; Khairuddin Khairuddin; M. Yamin (Postgraduate, University of Mataram, 2024)
Rawa Lake Taliwang is the lifeblood of the West Sumbawa Regency community. The lake is surrounded by extensive agricultural areas, making the activities of local farmers a significant contributor to the accumulation of heavy metals in the region. This study aims to determine the cadmium (Cd) content in snakehead fish (Channa striata ) and assess its suitability for consumption. Sampling was conducted using purposive sampling with direct observation at Lake Rawa Taliwang . Nets or traps were employed at two stations, with two replications at each station. Data analysis involved calculating the cadmium content in the laboratory using Atomic Absorption Spectroscopy (AAS). The results revealed that the cadmium concentration in snakehead fish from Lake Rawa Taliwang was 0.45 mg/kg (ppm). This concentration exceeds the permissible limit for metal contamination in food, as stated in BPOM Regulation Number 9 of 2022. As a result, the snakehead fish is deemed unfit for consumption.